RISK MANAGEMENT IN THE IMPLEMENTATION OF INVESTMENT AND CONSTRUCTION PROJECTS - I. Sokol (Вестник университета, 2017)
The article examines the problem of risk management in the implementation of investment and construction projects, proposed a comprehensive classification of risks, as well as a risk management mechanism for construction organizations. The approaches to risk management in the implementation of investment projects are outlined. Within the scope of the article, distinctive features of risk assessment methods are highlighted. Methods of analysis and evaluation of investment project risks are considered. Some of the existing methods of risk assessment are analyzed in terms of their advantages and disadvantages.